Development of a potential PET probe for HDAC6 imaging in Alzheimer's disease - Ping Bai; Prasenjit Mondal; Frederick A. Bagdasarian; Nisha Rani; Yan Liu; Ashley Gomm; Darcy R. Tocci; Se Hoon Choi; Hsiao-Ying Wey; Rudolph E. Tanzi; Can Zhang; Changning Wang (Elsevier, 2022)
Although the epigenetic regulatory protein histone deacetylase 6 (HDAC6) has been recently implicated in the etiology of Alzheimer's disease (AD), little is known about the role of HDAC6 in the etiopathogenesis of AD and whether HDAC6 can be a potential therapeutic target for AD. Here, we performed positron emission tomography (PET) imaging in combination with histopathological analysis to better understand the underlying pathomechanisms of HDAC6 in AD. We first developed [18F]PB118 which was demonstrated as a valid HDAC6 radioligand with excellent brain penetration and high specificity to HDAC6. PET studies of [18F]PB118 in 5xFAD mice showed significantly increased radioactivity in the brain compared to WT animals, with more pronounced changes identified in the cortex and hippocampus. The translatability of this radiotracer for AD in a potential human use was supported by additional studies, including similar uptake profiles in non-human primates, an increase of HDAC6 in AD-related human postmortem hippocampal tissues by Western blotting protein analysis, and our ex vivo histopathological analysis of HDAC6 in postmortem brain tissues of our animals. Collectively, our findings show that HDAC6 may lead to AD by mechanisms that tend to affect brain regions particularly susceptible to AD through an association with amyloid pathology.